Peer interviewers in mental health services research. Issue 4 (12th September 2016) - Croft, Bevin; Ostrow, Laysha; Italia, Linda; Camp-Bernard, Adrian; Jacobs, Yana
Abstract : Purpose: Inclusion of members of the target population in research is an increasing priority in the social sciences; however, relatively few studies employ approaches that involve persons with lived experience of the mental health system in mental health services research, particularly in the USA. The purpose of this paper is to describe one such approach, the employment of peer interviewers in the evaluation of a peer respite program. Design/methodology/approach: The paper describes how peer interviewers were recruited, hired, trained, and supervised. The authors discuss some benefits and challenges associated with the approach. Findings: Peer interviewer benefits and challenges: the shared lived experience between the peer interviewers and study participants contributed to increased comfort and a high response rate overall. The study opened up professional opportunities for peers, but inconsistent work hours were a challenge and resulted in turnover and difficulty filling vacant positions. The lead evaluator and supervisors worked closely with peer interviewers to ensure conflict of interest was mitigated to reduce bias. Originality/value: This paper adds to the limited literature describing peer representation in research, outlining one avenue for partnering with peers to align research with the values of the intervention under study without compromising – and perhaps increasing – scientific rigor. The authors expect that even more peer involvement in the oversight, analysis, and interpretation of results would have improved the overall quality of the evaluation. Future efforts should build upon and incorporate the approach alongside more comprehensive efforts to partner with service users.